Sulfated peptides: key players in plant development, growth, and stress responses - Zhang, Penghong; Zhao, Jiangzhe; Zhang, Wei; Guo, Yongfeng; Zhang, Kewei (Frontiers in Plant Science, 2024)
Phytohormones regulate plant development, growth, and stress responses. Of these, pPeptide hormones act, as an important class of small signaling molecules that, have been reported to work ato play a role at nanomolar concentrations. In Arabidopsis thaliana, sulfated peptides represent a class of proteins that undergo post-translational modification by Tyrosylprotein sulfotransferase (TPST), followed by specific enzymatic cleavage to generate mature peptides. This process contributes to the formation of various bioactive peptides, including PSKs (PHYTOSULFOKINEs), PSYs (PLANT PEPTIDE CONTAINING SULFATED TYROSINE), CIFs (CASPARIAN STRIP INTEGRITY FACTOR), and RGFs (ROOT MERISTEM GROWTH FACTOR). In the past three decades, significant progresses hasve been made in understanding the molecular mechanisms of the sulfated peptides that regulate plant development, growth, and stress responses. HereIn this review, we explore , we review the sequence properties of precursors, post-translational modifications, peptide receptors, and signal transduction pathways of the sulfated peptides, analyzing their functions in plants. with a particular, analysis ofzing their functions in plants. Moreover, tThe cross-talk between PSK/RGF peptides and other phytohormones, The cross-talk between PSK/RGF peptides and other phytohormones, 带格式的: 两端对齐 带格式的: 两端对齐 带格式的: 下划线 带格式的: 字体: (默认) Times New Roman such as brassinosteroids, auxin, salicylic acid, abscisic acid, gibberellins, ethylene, and jasmonic acid ， is also described. The significance of Altogether,The significance of the study of sulfated peptides in crops and their potential application toin enhance for enhancinging crop productivity are discussed, along with future research directions in the study of sulfated peptides.representsacts a significant milestone in this field of research. is discussed. The future studies in the field of sulfated peptides are prospected.